Music therapy with young people who have profound intellectual and developmental disability: Four case studies exploring communication and engagement within musical interactions. Issue Volume 40:Issue1(2015) (2nd January 2015) - Thompson, Grace A.; McFerran, Katrina Skewes
Abstract: Background The impact of music therapy on the communicative behaviours of young people with profound intellectual and developmental disability has not yet been established. Method Four adolescents participated in individual music therapy (MT) and toy play sessions with the same therapist in a 6-month period. Sessions were video-recorded and analysed based on The Inventory of Potentially Communicative Acts (Sigafoos, J., Arthur-Kelly, M., & Butterfield, N. (2006). Enhancing everyday communication for children with disabilities . Baltimore, MA: Brookes) to compare the communicative behaviours within each condition. Results Both conditions successfully engaged the young people, with slightly more communicative behaviours observed in MT in response to singing, and more rejecting behaviours in toy play. MT was therefore considered equivalent to toy play in terms of quantity, but distinctive in eliciting more mutually enjoyable interpersonal encounters. Conclusion MT creates engaging and motivating conditions for interactions with others, which suggests the need for greater integration of music therapy into special education classrooms.